Self-presentation and impression management: Understanding graphicon experience - Choi, Hwanho (Marketing Theory, 2024)
Prior studies suggest that the primary function of graphicons, such as emoji and stickers, is to enable more effective digital communication between individuals. In a digitally interactive environment, graphicons are an important means of expressing and exchanging sentiments, emotions, and thoughts. However, there is little understanding of the use of graphicons in the context of social and cultural conditions and their effect on impression management. Through analysis of in-depth interview data, the present study identifies three strategic applications of graphicons: social necessity, pursuit of social propriety, and expression of authentic self. Our findings suggest that individuals utilize various tools in the digital space to facilitate impression management. Graphicons are specifically used to convey relational meanings, and their usage is strongly related to social and cultural contexts and norms.
Keywords: digital interaction; emoji; emoticon; graphicons; Impression management; self-presentation